FUNGSI, TUJUAN DAN BENTUK-BENTUK PROMOSI - Lucy Indria Sari; Aisatun Nisa Fauziah; Ludina Risha Novia Arum Putri (Sekolah Tinggi Ilmu Ekonomi Darul Falah Mojokerto, 2024)
Promotion is a form of marketing communication that seeks to disseminateinformation, influence or persuade and remind the target market of thecompany and its products to be willing to accept, buy and be loyal to theproducts offered by the company concerned. The main functions ofpromotion activities are: (1) seeking and getting the attention of prospectivebuyers, (2) creating and cultivating